Joyful Learning Method to Create a Fun Classroom Atmosphere in Islamic Religious Education Learning at SMKN 3 Kota Bima - M. Yazid; Nuraini; Irwan (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The initial principle of education put forward by Ki Hajar Dewantara through Taman Siswa is education with an among system that optimizes the role of students through enjoyable learning. Therefore, learning aims to Build a Fun Classroom Atmosphere in Islamic Religious Education Learning. This Classroom Action Research aims to realize enjoyable learning by implementing Joyful Learning. The subjects of this study included 39 students. Data collection was taken through observation methods to measure the planning and implementation of learning with the Joyful Learning method, tests to measure the achievement of learning outcomes, questionnaire methods to measure student responses in participating in learning and documentation methods and interview methods to collect pre-cycle data. The results of the study concluded that the Joyful Learning Method for Building a Fun Classroom Atmosphere in Islamic Religious Education Learning at SMKN 3 Kota Bima. For the average evaluation results of cycle I was 81 with a classical completion percentage of 74%. While the average evaluation results of cycle II were 89 with a classical completion percentage of 89%. This means that the ideal classical completion target of 85% has been achieved. The percentage increase from cycle I to cycle II was 15%. Improvements were also evident from the teacher activity observation sheet results in cycle I, which showed 74%, categorized as fairly well implemented. This increased to 89% in cycle II, categorized as well implemented. The percentage increase from cycle I to cycle II was 15%. These results indicate that enjoyable learning can still be implemented and can produce positive impacts